2013
DOI: 10.15376/biores.8.4.6280-6287
|View full text |Cite
|
Sign up to set email alerts
|

Water Repellent Effect and Dimension Stability of Beech Wood Impregnated with Nano-Zinc Oxide

Abstract: The objective of this study was to quantify the influence of zinc oxide nanoparticles (nano-ZnO) on the water repellency and dimensional stability of beech wood. Beech wood blocks were treated with a nanoZnO solution at four treatment levels (0, 10,000, 20,000, and 40,000 ppm) using a modified dip method. Also, a thermal treatment was performed at 60 and 120 °C. After conditioning the samples, water absorption, volumetric swelling, water repellency effectiveness, and antishrink/anti-swell efficiency were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 11 publications
2
18
0
5
Order By: Relevance
“…It was revealed that 2 min immersion significantly reduced the water vapor sorption, as depicted in Figure 5. Similar findings were also reported elsewhere [57,72].…”
Section: Improvement Of Water Absorptionsupporting
confidence: 93%
See 1 more Smart Citation
“…It was revealed that 2 min immersion significantly reduced the water vapor sorption, as depicted in Figure 5. Similar findings were also reported elsewhere [57,72].…”
Section: Improvement Of Water Absorptionsupporting
confidence: 93%
“…A wide spectrum of organic, photocatalytic, and silver ion antimicrobial agents have been applied to date as coatings [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. This includes silver nanoparticles [52], combinations of various metal ions and various metalic nanoparticles [53,54], and combinations of all of the above [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]. Photocatalytic agents (e.g., titanium dioxide, ZnO) require conditions of water and oxygen and UV A wide spectrum of organic, photocatalytic, and silver ion antimicrobial agents have been applied to date as coatings [33][34][35][36][37][38][39][40][41][42]…”
Section: Increased Durabilitymentioning
confidence: 99%
“…Furthermore, Charyulu and Biswas () recommended the need for reduction in certification cost and gave more emphasis on investment in the research and development of organic farming for motivating farmers to pursue the organic way of farming. Soltani, Najafi, Yousefian, Naji, and Bakar () suggested that the government should provide subsidies, long‐term loans, and information about the technical and marketing issues in organic farming.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, Charyulu and Biswas (2010) recommended the need for reduction in certification cost and gave more emphasis on investment in the research and development of organic farming for motivating farmers to pursue the organic way of farming. Soltani, Najafi, Yousefian, Naji, and Bakar (2013) suggested that the government should provide subsidies, longterm loans, and information about the technical and marketing issues in organic farming. Demiryurek and Ceyhan (2008) found that the marketing aspect of organic farming is a major challenge; hence, farmers should not only focus on export but also need to strengthen the local and domestic markets through establishing cooperative and farmers association.…”
Section: Organic Farming and Marketing Challenges In Indiamentioning
confidence: 99%
“…The reduction in volumetric swelling with increasing nano-zinc oxide suggested that higher concentrations of ZnO provided substantial water resistance (SOLTANI et al, 2013). The improvement in dimensional stability samples containing ZnO can be attributed to the void being occupied by ZnO nanoparticles (RASHMI et al, 2012).…”
Section: Dimensional Stability Testmentioning
confidence: 99%